Association of sella turcica bridging with palatal canine impaction in skeletal Class I and Class II - Baidas LF; Al-Kawari HM; Al-Obaidan Z; Al-Marhoon A; Al-Shahrani S (Dove Medical Press, 2018)
Laila Fawzi Baidas,1 Huda Mohammad Al-Kawari,1 Zhara Al-Obaidan,2 Aqeelah Al-Marhoon,2 Sawsan Al-Shahrani2 1Department of Pediatric Dentistry and Orthodontics, College of Dentistry, King Saud University, Riyadh, Saudi Arabia; 2College of Dentistry, King Saud University, Riyadh, Saudi Arabia Purpose: Based on the evidence of the embryonic origin of the sella turcica and the teeth, this retrospective study evaluated the association between sella turcica bridging and palatal canine impaction in skeletal Class I and Class II orthodontic patients.Methods: Sixty-two orthodontic patients with palatally impacted canines and 54 controls with erupted canines (aged 12–25 years) were classified into skeletal Class I and Class II (according to ANB angle and Wits analysis). The length, depth, and diameter of the sella turcica were measured, and the shape was described. The difference in linear dimensions between the study and control groups was calculated using two-way analysis of variance and Student’s t-test. The interrelationship of the variables, subject groups, skeletal type, and age, with the linear dimensions of sella turcica, was tested using regression analyses. The association between sella turcica, bridging and palatally impacted canines was determined in skeletal type using a chi-square test.Results: Highly significant differences were found in the length, diameter, and depth of the sella turcica between the study sample and the control (P<0.001, P=0.015, P<0.0001, respectively). There was a highly significant frequency of bridging in cases with palatally impacted canines (P<0.0001). An increasing incidence of bridging was found in subjects with palatally impacted canines and skeletal Class I (P<0.0001) and Class II (P=0.044) relationships. Regression analysis showed that the age was significantly related to a change in length (P=0.025), diameter (P<0.0001), and depth (P<0.0001). The normal sella turcica morphology was present in most subjects (56.4%), and no significant association was found in subjects with palatally impacted canines in terms of the shape of the sella turcica.Conclusion: Sella turcica bridging is frequently seen in patients with impacted canines. The findings suggest that careful monitoring of canine eruption is required in patients diagnosed with sella turcica bridging at an early age. Keywords: sella turcica bridging, sella turcica shape, skeletal type, palatally impacted canine